1997
DOI: 10.1111/j.1432-2277.1997.tb00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of machine perfusion preservation on delayed graft function in non-heart-beating donor kidneys -early results

Abstract: Effect of machine perfusion preservation on delayed graft function in non-hearbbeating donor kidneysearly results AbstractThe functioning of nonheart-beating (NHB) donor kidneys upon transplantation is often delayed. To evaluate the effect of preservation by machine perfusion (MP) on early post-transplant function, 37 NHB donor kidneys were compared to 74 matched heartbeating (HB) donor kidneys preserved by cold storage (CS). The NHB donor kidneys were subject to 49 f 34 min of warm ischemia. Delayed function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…NHBD kidneys are routinely machine preserved. MP may reduce DGF and increase the rate of IF of renal allografts (25). In a meta-analysis of MP versus cold storage, MP leads to a 20% reduction in the incidence of DGF in HBDs and NHBDs.…”
Section: Discussionmentioning
confidence: 99%
“…NHBD kidneys are routinely machine preserved. MP may reduce DGF and increase the rate of IF of renal allografts (25). In a meta-analysis of MP versus cold storage, MP leads to a 20% reduction in the incidence of DGF in HBDs and NHBDs.…”
Section: Discussionmentioning
confidence: 99%
“…MP may reduce the DGF of grafts retrieved from heart-beating donors and donation after cardiac death (DCD) donors by 20% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Many authors have reported on the beneficial effects of MP on organs from marginal and DCD donors (33)(34)(35)(36)(37). Reports on renal allograft function in relation to preservation mode have focused on observations up to 12 months post-transplant (38)(39)(40)(41)(42) or have applied statistical simulation based on the relationship between function and graft survival and DGF (43)(44)(45)(46)(47) or the relationship between DGF and acute rejection (48).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, perfusion with HTK may allow for higher flows and also for more efficient cooling than UW, and has demonstrated superior properties to preserve ATP concentrations in the mild hypothermic range of 15-32 ° C, which is typically found in the initially cooling process during organ flushing [19,20] . In a protocol that applies kidney machine perfusion prior to transplantation, Daemen et al [21] have already demonstrated a possible benefit of combining HTK and UW for kidney preservation in non-heart-beating donors after warm ischemia. However, it is difficult to precisely characterize the exact influence of preservation solutions in the complex setting of machine perfusion.…”
Section: Discussionmentioning
confidence: 99%